Policing Rural Crime: The Case of the NSW Police Force Rural Crime Prevention Team - Whiteside, Cameron; Brennan, Ann; Mulrooney, Kyle (International Journal of Rural Criminology, 2023)
The NSW Police Force Rural Crime Prevention Team (RCPT) was created to prevent, disrupt, and respond to crimes that impact specifically on the agricultural, pastoral and aquaculture industries. Since its inception in early 2018, the team has developed and delivered a number of novel and innovative policing initiatives which seek to make rural communities safer and increase their resilience. In this paper, we offer practical insights on a number of these developments. Specifically, we will examine innovations deployed in relation to rural policing across five key areas, including 1) investigating rural crime within New South Wales and identifying interstate links and trends; 2) identifying inhibitors within legislation and policy impacting the ability of Law Enforcement Agencies to prevent, disrupt and respond to rural crime; 3) enhancing the education and knowledge of Law Enforcement Officers regarding rural crime; 4) raising the public awareness of rural crime and increasing community engagement with relevant stakeholders within rural communities and industries; and, finally, 5) collaborating and engaging with academic research/higher education toward the shared goal of safe rural spaces. We conclude the paper by discussing these practical developments in the context of farm crime research and, more specifically, how these collective efforts may serve to address established limitations and gaps in the policing and prevention of crime in rural spaces.